[tex]C=\dfrac{1}{f}=(n-1)\left(\dfrac{1}{R_1}-\dfrac{1}{R_2}\right)[/tex]
[tex]C=\dfrac{1}{f}=\dfrac{1}{x_1}+\dfrac{1}{x_2}[/tex]
În cazul de față, avem
[tex]R_1=R \\ R_2=-R[/tex]
[tex]n=1,5 \\ \beta =-3[/tex]
[tex]x_2=0.4 \ m[/tex]
[tex]\beta=\dfrac{x_2}{x_1} \ \ \ \ \Rightarrow \ \ \ x_1=\dfrac{x_2}{\beta}[/tex]
Înlocuim în a doua ecuație de la început:
[tex]\dfrac{1}{f}=\dfrac{\beta+1}{x_2}[/tex]
Prima ecuație devine:
[tex]\dfrac{\beta+1}{x_2}=(n-1)\cdot \dfrac{2}{R} \ \ \ \ \ \Rightarrow \ \ \ R=\dfrac{2x_2(n-1)}{\beta+1}[/tex]